2012
DOI: 10.1177/030089161209800614
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of vascular endothelial growth factor and endostatin in urine for diagnosis of bladder cancer

Abstract: Urine levels of VEGF and endostatin may be a clinically useful aid in the diagnosis of bladder cancer, and endostatin but not VEGF is a supplementary prognostic marker for predicting tumor progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…These studies further illustrate the roles and balance of both positive and negative regulatory factors in tumor angiogenesis [5]. Studies have also indicated the potential of endostatin as a marker of prognostic value in hepatocellular carcinoma [197], bladder cancer [200], cervical cancer [204], colorectal cancer [208], nasopharyngeal carcinoma [211], bronchopulmonary dysplasia [219], pulmonary arterial hypertension [214], traumatic brain injury [217], intermittent claudication in peripheral vascular disease [270], benign vs. malignant ascites [271], Alzheimer’s disease [216], and chronic kidney disease [196]. …”
Section: Discussionmentioning
confidence: 89%
“…These studies further illustrate the roles and balance of both positive and negative regulatory factors in tumor angiogenesis [5]. Studies have also indicated the potential of endostatin as a marker of prognostic value in hepatocellular carcinoma [197], bladder cancer [200], cervical cancer [204], colorectal cancer [208], nasopharyngeal carcinoma [211], bronchopulmonary dysplasia [219], pulmonary arterial hypertension [214], traumatic brain injury [217], intermittent claudication in peripheral vascular disease [270], benign vs. malignant ascites [271], Alzheimer’s disease [216], and chronic kidney disease [196]. …”
Section: Discussionmentioning
confidence: 89%
“…Studies have also investigated concentrations of endothelial markers involved in angiogenesis, tumour tissues, blood circulation and concentrations in urine. [20][21][22] An increase is seen in concentrations in general circulation of molecules whose expressions increase for various reasons in the vascular endothelium. At the same time, increasingly expressed molecules may also infiltrate urine from the vascular endothelium on the bladder wall.…”
Section: Discussionmentioning
confidence: 99%
“…32 Studies have also investigated levels of endothelial markers involved in angiogenesis, tumor tissues, blood circulation, and levels in urine. 33,34 Zhang et al 35 showed that endocan is expressed in neogenically active tissue and cell types. They also suggested that endocan may be an important marker in angiogenesis and neogenesis.…”
Section: Discussionmentioning
confidence: 99%